Oral arsenic trioxide for treating acute promyelocytic leukaemia: Implications for its worldwide epidemiology and beyond - Kumana, Cyrus R.; Kwong, Yok-Lam; Gill, Harinder (Frontiers in Oncology, 2022)
This account explores: 1) How orally administered Arsenic-trioxide (ATO) therapy influences the epidemiology of acute promyelocytic leukaemia (APL), and 2) How the experience that ensue may expand the indications for oral ATO as a treatment for diseases/disorders other than APL. Over the last two decades, experience with APL patients in Hong Kong treated with an oral regimen termed AAA (consisting of ATO, all-trans retinoic acid [ATRA], and ascorbic acid) has confirmed a dramatic improvement in overall survival. Over that period, there has been an estimated 60-fold increase in the prevalence of APL. In contrast to regimens entailing intravenous (IV) ATO, the consequential therapeutic benefits of using oral ATO have been achieved with much less patient inconvenience and quality of life disruption, reduced burdens on health care facilities (hospitalisations & staff involvement), and much enhanced affordability (retail drug & other cost reductions). Furthermore, numerous experimental and a few clinical studies suggest that ATO may also have a therapeutic role in many other diseases/disorders. Several such diseases (e.g. autoimmune disorders & idiopathic pulmonary fibrosis) are far more prevalent than APL, which means that very large numbers of patients may potentially benefit from ATO treatment even if its efficacy is limited to selected populations with these diseases. The known safety of oral ATO and its advantages over repeated long-term IV delivery suggests that this route be used in future clinical studies of its possible role in such diseases. Thus, if the clinical utility of oral ATO treatment is validated in these diseases, potentially much large numbers of patients with non-APL diseases may stand to benefit.